Prevalence of Brief Atrial Fibrillation in Ischaemic Stroke and Transient Ischaemic Attack - The MY-ATRIA Study: Rationale and Design - Ricardo, Salinas-Martínez; Anna, Zaniboni; Laura, Piccolo; Ludovica, Migliaccio; Lorenza, Rubini; Letizia, Riva; Ambra, Fiorani; Matteo, Paolucci; Mauro, Gentile; Stefano, Forlivesi; et al. (Cardiology and Cardiovascular Medicine, 2026)
Background: Recent studies suggest that brief atrial fibrillation (BAF, episodes shorter than 30 seconds) comprises 52% of all newly detected atrial fibrillation (AF) in patients with ischaemic stroke (IS) and transient ischaemic attack (TIA) without AF history. However, variations in monitoring strategies could have led to under- or overestimating the prevalence of BAF. Objective: Our study seeks to improve detections rates by adhering to recommendations from previous research, including prolonged cardiac monitoring, initiating monitoring shortly after ischaemic event and increased sample size. Methods: The MY-ATRIA study is a single-center observational and transversal prospective study aiming to determine the prevalence of BAF episodes in patients with recent IS or TIA (indexing event) without AF history by performing 7-day Holter cardiac monitoring. Results: We screened 637 patients with mean age of 70.3 ± 13.8 years, male predominance (58.9%, 375/637), and the majority with IS (96.5%, 615/637). The mean time interval from indexing event to enrollment was 2.29 ± 1.62 days and Holter monitoring started as soon as possible and no later than 7 days after indexing event. Conclusion: This study will contribute to measuring the prevalence of IS or TIA patients with BAF episodes and the proportion of BAF episodes among all detected AF episodes. This is a step forward in determining whether BAF episodes represent an independent risk factor for thromboembolism and whether they warrant the same treatment as clinical AF. Registered on ClinicalTrials.gov (NCT04963647)